2012
DOI: 10.1016/j.compstruct.2011.11.021
|View full text |Cite
|
Sign up to set email alerts
|

The influence of acrylate triblock copolymer embedded in matrix on composite structures’ responses to low-velocity impacts

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. In passive safety structures the use of composite materials has increased significantly recently due to their low specific mass and high energy absorption capacities. The purpose of this experimental study is to describe the macroscopic behaviors of different Kevlar woven composite materials with different kinds of matrix (pure and with acrylate based block cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…For the resin with nano-reinforcements, 10 g of triblocks copolymer M52N Nanostrength Ò supplied by Arkema was added to 100 g of Epolam resin. Denneulin et al have shown from tests on Kevlar composites with three different formulations of block copolymer (M22, M42, and M52N) that 10% M52N Nanostrength Ò in the epoxy resin system provided the best performance with regard to perforation resistance [16]. Nanostrength Ò which is in powder form is added to the resin by mixing, using a mechanical stirrer at 290 rpm at 110°C for a duration of 2 h. Transmission Electronic Microscopy (TEM) was used by Denneulin et al [16] to check the self-assembling process of the block copolymer nanoparticles.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…For the resin with nano-reinforcements, 10 g of triblocks copolymer M52N Nanostrength Ò supplied by Arkema was added to 100 g of Epolam resin. Denneulin et al have shown from tests on Kevlar composites with three different formulations of block copolymer (M22, M42, and M52N) that 10% M52N Nanostrength Ò in the epoxy resin system provided the best performance with regard to perforation resistance [16]. Nanostrength Ò which is in powder form is added to the resin by mixing, using a mechanical stirrer at 290 rpm at 110°C for a duration of 2 h. Transmission Electronic Microscopy (TEM) was used by Denneulin et al [16] to check the self-assembling process of the block copolymer nanoparticles.…”
Section: Methodsmentioning
confidence: 99%
“…1. The manufacturing process was similar to the method explained in [16]. In the first step, each layer of Kevlar fabric cut to desired dimensions was impregnated with the resin-hardener mix manually (with a brush).…”
Section: Methods Of Fabricationmentioning
confidence: 99%
See 3 more Smart Citations